Merajut Manajemen Negara dalam Bingkai Nasionalisme Humanis - Sabiqul Khair syarif (Universitas Islam Indonesia, 2005)
Up to now, the discourse of the Indonesian nationalism development is still going on. Debates and questions on this issue tend to show that the birth of Indonesia was based on the porous nationalism. It was accumulated with the emerging several centrifugal conflicts in this country triggered by the issues of religions, ethnic, etc like what had taken place in Ambon, Sampit, Sambas, and Aceh. This paper discusses the concept of dynamic nationalism that should be earthed through the dialectic process from time to time. Models of repressive ideologies and political mobilization must be eliminated. For example, the collapse of Soviet Union and Yugoslavia were lesson that could be leamed from this issue. The future face of the Indonesian nationalism should be based on the human right without any forces, violence, exploitation, and suppression.